School Effectiveness: Institutional Benchmarking for Vocational High School Management - Prasetyo, Muhammad Anggung Manumanoso; Salabi, Agus Salim (LPPM Undiksha, 2023)
The disruption era presents a challenge for schools in the form of educational graduate standards in comparison to industry and the workforce. The government responded by instituting a policy of vocational schools to produce superior human resources. The adaptive strategy implemented is one of long-term quality improvement through the measurement of organizational performance using benchmarking models. The study aims to analyze the effectiveness of benchmarking techniques in improving educational services in Public Vocational High School. The research is qualitative in nature, employing case study techniques. The veracity of the data is checked using sources of principals, school public relation, and senior teacher. Data triangulation techniques and peer discussion were used to examining the data. The study's findings demonstrate technical benchmarking implementation through planning, analysis, integration, implementation, and maturity is known as institutionalist benchmarking. Benchmarking strategies for sustainable organizations are implemented concurrently through vision adaptation, mission and objectives toward strategic environments; benchmarking targeting focus determination, and goal determination through the fabric of school superior partnerships. Adaptation of the benchmarking outcomes program results in actualizing educational information system management, peer tutoring techniques, optimization of research activities, and strengthening internal supervision. In addition, interviews are the only method used to collect data for this study. Therefore, future research will investigate the school institution of others in Indonesia, particularly the development of vocational schools that have already integrated science and skill competencies.